Practice development in social work: differences between social workers with a bachelor's and master's degree. - van Pelt, Mariël; Sleegers, Peter; Roose, Rudi; Hutschemaekers, Giel (European Journal of Social Work, 2024)
A process of academisation in social work is going on in Europe, as illustrated by the establishment of master's programmes in social work (MSW programmes) at Dutch universities of applied sciences. These programmes prepare social workers for systematically improving their practice. The goal of this study is to examine the differences between bachelor's- and MSW-educated social workers in the extent to which they engage in social practice development (SPD) activities, including linking, cooperation, evidence-based practice (EBP) and reflexivity, in daily practice. Data were collected from a survey among professionals with a MSW degree (N = 54), bachelor SW degree (N = 89) and MSW students (N = 43). The results show that social workers engage in SPD activities, however to a modest extent. MSW-educated social workers engage in significantly more EBP and Reflexivity than professionals with a bachelor's degree. After controlling for working experience and main task, education levels alone appear to have a significant effect on the application of EBP. To stimulate SPD and practice improvement, further development of MSW programmes is needed, the influx of social workers in MSW programmes must increase substantially and employers should facilitate social workers to engage in SPD by task or function differentiation.